PENGARUH VARIASI DIAMETER PULI TERHADAP KONSUMSI BAHAN BAKAR MESIN PEMIPIL JAGUNG TIPE MCT 5-60 - Ramadhani, Adi Setiawan (Politeknik Harapan Bersama Tegal, 2023)
Abstract Corn is one of the main ingredients that can be processed into several types of food to meet the needs of the community. The process of processing corn using tools is growing rapidly along with technological advances so as to provide convenience for the community, especially farmers, in processing agricultural products. The machine used is a sheller type which is expected to reduce long processing times and save fuel costs if used in the long term. The purpose of this study was to determine the effect of variations in pulley diameter on fuel consumption of the MCT 5-60 corn sheller engine using a Mct 5-60 15 sheller engine and an additional GX 160 diesel engine with a power of 5.5 PK for the purpose of experimenting data collection with pulley 2 inch, 2.5 inch, and 3 inch with a fixed rpm of 1500 at the time of this test with 3 trials each. Specific fuel consumption is defined as the amount of fuel used to produce a unit of power to determine the effect of variations in pulley diameter on fuel consumption. The test method uses the experimental method, namely by changing the variation of the diameter of the pulley on the engine that is driven with a load of 3 kg, the diameter of the pulley is 2 inch, the fuel is 16 ml and the average time is 2.27 minutes, the pulley is 2.5 inch the average material burn 12 ml and the average time is 1.22 minutes. The 3 inch pulley is 5 ml and the average time is 1.04 minutes. and the size of the diameter of the pulley which is driven by a 4.5 inch diameter engine and the best results on a 3 inch diameter pulley with an average fuel consumption of 5 ml and an average testing time of 1.04 minutes.